Students’ Difficulties with Vocabulary Mastery in English Language Education at the University Level - Harselina, Harselina; Idayani, Andi; Sailun, Betty (UIR Press, 2024)
Vocabulary mastery is crucial for facilitating the acquisition of language skills. This research aims to identify students' difficulties with vocabulary mastery in English Language Education at the university level. A quantitative research approach was used, focusing on first-semester students in Class A as the research sample and Class B for test trials. The sample consisted of 33 students (13 males and 20 females) from the English Language Education program at FKIP Universitas Islam Riau. The study employed a vocabulary test in multiple-choice format, and simple purposive sampling was used to distribute the test. The test link was shared via the class chairman, and SPSS version 25 was used for data analysis. The research identified students' difficulties in vocabulary mastery through their test results. The results indicated an average student score of 69, categorized as